2016
DOI: 10.1128/genomea.01262-16
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Bellavista Virus, a Novel Orthobunyavirus Isolated from a Pool of Mosquitoes Captured near Iquitos, Peru

Abstract: A novel orthobunyavirus, Bellavista virus, was isolated from Culex (Melanoconion) portesi mosquitoes in the Bellavista neighborhood of Iquitos, Peru, in 2009. The assembled segment L, M, and S sequences of strain PRD0552 are 6,950, 4,469, and 1,256 bases in length, respectively, comprising complete protein-coding sequences and partial terminal untranslated sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Mosquitoes of the Culicidae family represent a threat to public global health, especially in tropical and subtropical regions, where they participate as the main vectors in the transmission of infectious agents that affect humans and animals. Of the circa 3700 species of mosquitoes worldwide, 1069 species are registered in the neotropical region (Wilkerson et al, 2021), of which in Peru, 182 species have been o cially reported; of these, 44 belong to the genus Culex Linnaeus, 1758 (Ayala et al, 2020(Ayala et al, , 2021) and many of these are considered arbovirus vectors, especially the species of the subgenus Melanoconion (Turell et al, 2005;Yanoviak et al, 2005;Turell et al, 2006Turell et al, , 2008Evangelista et al, 2013;Hang et al, 2016;Treangen et al, 2016;Turell et al, 2021). In Peru, the arboviruses transmitted by Culex spp.…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes of the Culicidae family represent a threat to public global health, especially in tropical and subtropical regions, where they participate as the main vectors in the transmission of infectious agents that affect humans and animals. Of the circa 3700 species of mosquitoes worldwide, 1069 species are registered in the neotropical region (Wilkerson et al, 2021), of which in Peru, 182 species have been o cially reported; of these, 44 belong to the genus Culex Linnaeus, 1758 (Ayala et al, 2020(Ayala et al, , 2021) and many of these are considered arbovirus vectors, especially the species of the subgenus Melanoconion (Turell et al, 2005;Yanoviak et al, 2005;Turell et al, 2006Turell et al, , 2008Evangelista et al, 2013;Hang et al, 2016;Treangen et al, 2016;Turell et al, 2021). In Peru, the arboviruses transmitted by Culex spp.…”
Section: Introductionmentioning
confidence: 99%